Outer Factors of Meiji Japan’s Fast Modernization at the End of the 19th Century - U. E. Mamytov (Евразийская интеграция: экономика, право, политика, 2022)
The end of the globalization and the rise of the “curtain wall” between the West and Russia again raises the question of economic and technological backwardness of Eurasian Union countries comparing to the “developed countries”, and especially the backwardness of such countries as Kyrgyzstan. That fact is sufficiently connected to sometimes extremal concentration on inner problems, which prevents the state and inner community to set pragmatic aims of rapid technological and economic development. In this context the experience of fast catch-up of Japan at the end of the 19th century gives a good example how that can be realized. And that Japanese experience is still looks actual, despite that it happened almost 150 years ago.Aim. An evaluation of the affection of outer factors in Meiji Japan’s fast economic catch-up.Tasks. For those purposes were analyzed the reasons of fast economic development, as well as the factors which stimulated Japan’s modernization.Methods. As a methodology there was used an analysis of economic, technological and ideological factors.Results. Results of the research demonstrate that, first, the fast catch-up itself was pushed by outer threats of getting into colonial dependency of the Western countries, and second, for fast development Japan pragmatically used Western technologies.Conclusion. Technological modernization should become the basic factor for rapid economic development of the Eurasian Union countries, and the state can play certain coordinating role in such a process sometimes using ideological factors.